2015
DOI: 10.1186/s13071-015-1109-6
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic speciation in the Triatoma sordida subcomplex (Hemiptera, Reduviidae) revealed by chromosomal markers

Abstract: BackgroundChagas disease vectors (Hemiptera-Reduviidae) comprise more than 140 blood-sucking insect species of the Triatominae subfamily. The largest genus is Triatoma, subdivided in several complexes and subcomplexes according to morphology, ecology and genetic features. One of them is the sordida subcomplex, involving four species: Triatoma sordida, T. guasayana, T. garciabesi and T. patagonica. Given the great morphological similarity of these species, their taxonomic identification, evolutionary relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
79
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 31 publications
3
79
0
3
Order By: Relevance
“…sordida sensu stricto and a new putative species T . sordida Argentina (5.3%) [20], but lower than reported to separate closely related triatomine species (7.1%) [23]. Considering that the persistence of gene flow among populations is unlikely, this nucleotide divergence might be due to several causes: a recent North-South dispersion process, and/or adaptive genetic changes associated with different ecological or environmental conditions.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…sordida sensu stricto and a new putative species T . sordida Argentina (5.3%) [20], but lower than reported to separate closely related triatomine species (7.1%) [23]. Considering that the persistence of gene flow among populations is unlikely, this nucleotide divergence might be due to several causes: a recent North-South dispersion process, and/or adaptive genetic changes associated with different ecological or environmental conditions.…”
Section: Discussionmentioning
confidence: 88%
“…Although C-heterochromatin polymorphism is frequently observed in several triatomine species [18], the pronounced autosomal differences observed among North (35% of C-content) and South (0%) individuals had not been described in conspecific populations. Variations of this magnitude have only been detected among sibling Triatoma species from North [39] and South America [19,20,31]. Extensive literature describes possible effects and adaptive functions of heterochromatin on both of plants and animals [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations may even include cryptic (morphologically identical but genetically different) species e.g. (Panzera et al, 2015). And, as closely related taxa usually share similar traits, understanding the degree of relatedness amongst different taxa allows one to predict traits.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Currently, there are 152 species of triatomines, distributed in 18 genera and five tribes, all species being considered as a potential vector of Chagas disease. 4,5 Although the evolutionary process in triatomine is considered as disruptive (occurs when extreme phenotypes have a fitness advantage over more intermediate phenotypes) by Dujardin et al, 6 cryptic speciation (morphologically identical populations that are reproductively isolated and successfully differentiated by molecular data) has been detected for some species (for example, Triatoma sordida [Stål, 1859] 7 and Triatoma dimidiata [Latreille, 1811] 8 ), and Costa et al 9 also suggested homoploid hybridization (derived species by hybridization without a change in chromosome number) as a possible mode of speciation in Triatominae. By means of morphometrics, 9 morphological, 9 ecological, 10 geographic, 10 isoenzymes, 11 cross-experimental, 12 and molecular analyses, 13 it was suggested that Triatoma brasiliensis macromelasoma Galvão, 1956 could be a product of hybridization between Triatoma brasiliensis Neiva, 1911 and Triatoma juazeirensis Costa and Félix, 2007. Recently, Costa et al 14 observed intermediate chromatic phenotypes for T. b. macromelasoma in various locations in areas between the T. brasiliensis and T. juazeirensis occurrences and suggested that these data, combined with molecular analysis and experimental crosses, support the distinction of a zone of hybridization (Pernambuco state, Brazil) that gave rise to the T. b. macromelasoma through homoploid evolution.…”
mentioning
confidence: 99%